2023
DOI: 10.1371/journal.pcbi.1011483
|View full text |Cite
|
Sign up to set email alerts
|

Measuring uncertainty in human visual segmentation

Jonathan Vacher,
Claire Launay,
Pascal Mamassian
et al.

Abstract: Segmenting visual stimuli into distinct groups of features and visual objects is central to visual function. Classical psychophysical methods have helped uncover many rules of human perceptual segmentation, and recent progress in machine learning has produced successful algorithms. Yet, the computational logic of human segmentation remains unclear, partially because we lack well-controlled paradigms to measure perceptual segmentation maps and compare models quantitatively. Here we propose a new, integrated app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…formulated style transfer as an optimization problem minimizing the distances between Gram matrices of VGG features [GEB16]. Other global statistics have been proven effective for style transfer and texture synthesis such as deep correlations [SC17; GGL22], Bures metric [VDKC20], spatial mean of features [LZW16; DDD*21], feature histograms [RWB17], or even the full feature distributions [HVCB21]. Specific cost function corrections have also been proposed for photorealistic style transfer [LPSB17].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…formulated style transfer as an optimization problem minimizing the distances between Gram matrices of VGG features [GEB16]. Other global statistics have been proven effective for style transfer and texture synthesis such as deep correlations [SC17; GGL22], Bures metric [VDKC20], spatial mean of features [LZW16; DDD*21], feature histograms [RWB17], or even the full feature distributions [HVCB21]. Specific cost function corrections have also been proposed for photorealistic style transfer [LPSB17].…”
Section: Related Workmentioning
confidence: 99%
“…NST is performed by optimizing a functional aiming at a compromise between fidelity to VGG19 features of the content image while reproducing the Gram matrices statistics of the style image. Other global statistics have been proven effective for style transfer and texture synthesis [LZW16; SC17; LPSB17; VDKC20; RWB17; HVCB21; DDD*21; GGL22] and it has been shown that a coarse‐to‐fine multiscale approach allows one to reproduce different levels of style detail for images of moderate to high‐resolution (HR) [GEB*17; Sne17; GGL22]. The two major drawbacks of such optimization‐based NST are the computation time and the limited resolution of images because of large GPU memory requirements.…”
Section: Introductionmentioning
confidence: 99%